Mind the gap: What code-switching in literature can teach us about code-switching. (August 2015) - Weston, Daniel; Gardner-Chloros, Penelope
This article argues that contrary to sociolinguistic practice which emphasizes spontaneous speech as the main or only source of evidence, the study of literary code-switching (CS) can be relevant to an understanding of CS in general. CS is first distinguished from other forms of literary multilingualism and from borrowing. We then consider how CS fits in with the mimetic function in literary dialogue, and how its functions can be compared with those of natural speech. We will see that literary CS can provide a wealth of sociolinguistically relevant information on speech modes found in various communities, and is particularly apt to portray postcolonial tensions. More stylized CS in poetry and drama can also embody complex multicultural identities and patterns of language choice, even in the absence of strict verisimilitude.